CEO share ownership, compensation and firm performance: Evidence from Finland 2015-2020 - Silander, Matias (My University, 2022)
This thesis examines the effect of CEO compensation and share ownership on firm performance. CEO compensation and share ownership is widely studied in the US and UK but there is a lack of studies in the Nordics. Therefore, this thesis uses a panel data of Finnish listed companies between the years 2015 – 2020. First, the effect of CEO fixed compensation on firm operating performance and valuation is examined. Next, the effect of CEO variable compensation and share-based compensation are studied. Last, the association between CEO share ownership and firm performance and valuation are examined. Operating performance is measured as return on assets and return on equity, and valuation as Tobin’s Q. This thesis finds that CEO fixed compensation is negatively related to the valuation of the firm whereas variable compensation and share-based compensation have significant positive effect on firm valuation. Moreover, the economic effect of share-based compensation is stronger than the effect of total variable compensation. Controversially, higher CEO share ownership does not have an effect on firm valuation. The evidence of the association between CEO compensation and firm operating performance are mixed. Variable and share-based compensation have a positive effect on return on assets but no effect on return on equity. In addition, CEO share ownership is positively related to return on equity. These findings provide useful information for future equity compensation research in the Nordics.
Keywords: omistajaohjaus; compensation (activity); palkitseminen; omistus; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance